THE ROLE OF THE TEACHER IN HIGHER LEGAL EDUCATION AND THE IMPACTS ON THE STUDENT’S ACADEMIC TRAINING - Lima e Silva, Charles; Elizabeth Rees de Azevedo, Karin (Revista Gênero e Interdisciplinaridade, 2023)
This article aims to analyze the role of the teacher in Higher Legal Education regarding its contribution to the academic training of students, as well as the impacts and repercussions on the learning of these students. Thus, it is necessary to verify about the performance of teachers, in the pedagogical relationship between teaching and learning. Thus, this text starts from the formation of a didactic of Higher Legal Education, which is a pedagogical reference, in order to understand the social functioning of this and with the following problem: what are the impacts of the didactics of Higher Legal Education in the academic formation of students? The methodology used involves the techniques of documental, statistical and bibliographic review analysis characteristic of qualitative research, which communicates the ideas of pedagogical didactics and practical knowledge. To this end, a study of the main aspects related to the theme was carried out, aiming, at the end, to demonstrate that the reflections on the inter-relationship between student and teacher, which lead to the need of joint elaboration are didactic-methodological tools and strategies that improve the quality in the teaching process and learning of Law Courses. The result is also the contribution to the strengthening of knowledge, with the realization of the social right to education, through the constitutional means necessary to guarantee these, in search of a higher legal education of quality.